2020
DOI: 10.1007/s00125-020-05163-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific associations of insulin resistance with chronic kidney disease and kidney function: a bi-directional Mendelian randomisation study

Abstract: Aims/hypothesis Reasons for the sexual disparity in chronic kidney disease (CKD) are unclear. To provide insight we contextualised these differences within evolutionary biology, and explored sex-specific effects of insulin resistance because it may have sex-specific effects on the reproductive axis. Impaired kidney function may also cause insulin resistance. We assessed these possibilities using bi-directional, sex-specific, two-sample Mendelian randomisation (MR). Methods Given that fasting insulin, fasting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Our null findings for genetically predicted FG and HbA 1c in relation to chronic kidney disease agree with the results of previous MR studies (18). Although we observed a positive association between genetically predicted FI and chronic kidney disease, this association seemed to be sex specific (17). Given lack of sex-specific data on chronic kidney disease in the used data sets, we could not confirm this sex-specific association.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our null findings for genetically predicted FG and HbA 1c in relation to chronic kidney disease agree with the results of previous MR studies (18). Although we observed a positive association between genetically predicted FI and chronic kidney disease, this association seemed to be sex specific (17). Given lack of sex-specific data on chronic kidney disease in the used data sets, we could not confirm this sex-specific association.…”
Section: Discussionsupporting
confidence: 54%
“…In previous MR studies investigators have found a consistent influence of certain glycemic traits, such as glucose and glycated hemoglobin (HbA 1c ), on risk of coronary artery disease (9)(10)(11)(12)(13). Nevertheless, results of studies of the associations of glycemic traits with other atherosclerotic diseases, such as ischemic stroke (13)(14)(15)(16) and chronic kidney disease (17)(18)(19), were inconsistent, and there is a scarcity of data on the MR associations for peripheral artery disease as well as other atherosclerotic and thrombotic outcomes (13).…”
mentioning
confidence: 99%
“…Analyses of the UK biobank provided a great contribution to the prognostic research in CKD. For example, genetically predicted testosterone and fasting insulin, with the latter being an expression of insulin resistance, were found to be associated with CKD and worse kidney function in men, thus highlighting the possible reasons for discrepancy in CKD prevalence and CKD progression among men and women [84,85]. Intriguingly, a genome-wide association study of UK biobank showed that albumin-to-creatinine ratio (ACR) is dependent on multiple pathways and that an ACR genetic risk score may improve the prediction of hypertension and stroke [86].…”
Section: Prognostic Role Of Proteomics Metabolomics and Genomicsmentioning
confidence: 99%
“…Based on further MR reports, genetically-predicted higher SHBG may lower insulin resistance and T2D risk in men and women ( 49 51 ). Moreover, in men, elevated fasting insulin has been linked to impaired kidney function, but not vice versa ( 52 ). Further studies that can provide sex-specific mechanistic insights to the SHBG-kidney relationship are warranted.…”
Section: Discussionmentioning
confidence: 99%